Analysis of Financial Performance Assessment Using the Economic Value Added (EVA) Method (Study at Bank Muamalat Indonesia 2019-2021) - Annisa Preity Awalia; Marliyah Marliyah; Muhammad Lathief Ilhamy (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Evaluation and measurement of financial performance can be assessed using financial ratios. However, management performance and achievements as measured by financial ratios are considered to be less representative of the actual state of the company. So another approach is needed, one of which is the Economic Value Added (EVA) approach. The EVA method can complement the lack of financial ratios and is more accurate in measuring performance and calculating the added value created by the company. This study aims to determine the financial performance of PT Bank Muamalat Indonesia Tbk during 2019-2021 and to analyze financial performance using theEconomic Value Added (EVAs). The type of data used is secondary data that is qualitative in nature taken from the annual report of PT Bank Muamalat Indonesia Tbk for the 2019-2021 period using the documentation data collection method. Based on analysis and calculation sEconomic Value Added (EVA) PT Bank Muamalat Indonesia Tbk in 2019-2021 shows a positive EVA value or (EVA > 0), which means that the financial performance of Bank Muamalat is in good health so that the bank is able to generate added value or profit generated sufficient to cover its operational costs so that the financial performance the company is in an advantageous position.